High T3 Induces β-Cell Insulin Resistance via Endoplasmic Reticulum Stress - Bo Liang; Liyun Liu; Huibin Huang; Liangyi Li; Jingxiong Zhou (Mediators of Inflammation, 2020)
Hyperthyroidism can cause glucose metabolism disorders and insulin resistance. Insulin resistance in muscle and adipose tissues has been extensively studied, whereas investigations on β-cell insulin resistance are limited. This study preliminarily explored the effects of high T3 levels on β-cell line (MIN6) insulin resistance, as well as the roles of endoplasmic reticulum stress (ERS). In this study, we treated β-cell line with T3, with or without an inhibitor of phosphotyrosine phosphatases (PTPs, sodium vanadate) or ERS inhibitor (4-PBA). The results indicated that high levels of T3 significantly inhibited insulin secretion in β-cell line. In addition, we observed an upregulation of p-IRS-1ser307 and downregulation of Akt. These results can be corrected by sodium vanadate. Moreover, high T3 levels upregulate the ERS-related proteins PERK, IRE1, ATF6, and GRP78, as well as ERS-related apoptosis CHOP and caspase-12. Similarly, this change can be corrected by 4-PBA. These results suggest that high T3 levels can induce insulin resistance in β-cell line by activating ERS and the apoptotic pathway.